1997
DOI: 10.1007/s11746-997-0014-3
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of γ‐linolenic acid from borage oil via lipase‐catalyzed reactions

Abstract: Three lipase-catalyzed reactions were utilized to enrich γ-linolenic acid in borage oil: (i) selective hydrolysis in isooctane by Candida rugosa lipase immobilized on microporous polypropylene, (ii) selective esterification of free fatty acid from saponified borage oil and n-butanol by Lipozyme IM-20, and (iii) acidolysis of the products of the previous two reactions, that is, unhydrolyzed acylglycerols and unesterified free fatty acid. In the selective hydrolysis, γ-linolenic acid content could be raised from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 22 publications
1
33
2
Order By: Relevance
“…On the other hand, products with 65% GLA in their acylglycerol fraction have been achieved employing acidolysis processes [91] with borage oil as starting material.…”
Section: Enzymatic Methodsmentioning
confidence: 99%
“…On the other hand, products with 65% GLA in their acylglycerol fraction have been achieved employing acidolysis processes [91] with borage oil as starting material.…”
Section: Enzymatic Methodsmentioning
confidence: 99%
“…Lipase-catalyzed esterification was employed for the enrichment of GLA from borage oil fatty acid, and free fatty acids (FFA) with a GLA content of ca. 90% were obtained (10,11). By a two-step process, which involved enzyme-catalyzed hydrolysis of borage oil and the esterification of the resulting FFA with lauryl alcohol, a 93.7% GLA content in FFA with a corresponding yield of 67.5% was obtained (12).…”
mentioning
confidence: 99%
“…HPLC and UV-VIS spectrophotometric analysis showed that the maximum conversion was observed in Treatment 23 (OT 23 -5.720%) which was significantly more than the other treatments (P>0.05). The percentage of conversion of lutein ester was 38.7% as indicated by HPLC for OT 23 . The mean difference between OT 31 and OT 20 was more than the critical difference at 5% level of significance and hence the OT 31 yielded significantly more conversion than OT 20 .…”
Section: Effect Of Phmentioning
confidence: 92%
“…Hydrolysis activity of the CALB lipase was assayed titrimetrically on olive oil emulsion [23]. The immobilized lipase was added to 10 ml of 10% v/v olive oil emulsion and was preincubated at 37°C for 20 min.…”
Section: Determination Of Lipase Activitymentioning
confidence: 99%
See 1 more Smart Citation